Efektivitas model PBL-GI dalam meningkatkan literasi sains pada materi kesetimbangan kimia di SMA - Mutmainnah; Mardhiya, Julia; Nugroho, Deni Ebit (Universitas Papua, Manokwari, Indonesia, 2025)
Ideally, students should have scientific literacy skills to understand and apply chemical concepts in real life. Students' scientific literacy is still low, especially in understanding abstract chemical equilibrium material. This study aims to analyze the effectiveness of the Problem-Based Learning-Group Investigation (PBL-GI) model in improving students' scientific literacy in chemical equilibrium material. This study used a quasi-experimental method with a nonequivalent control group design. The sample was selected using the cluster random sampling technique, and data were collected through test and non-test techniques. The results of the study showed that the PBL-GI model was effective in improving students' scientific literacy, as evidenced by the results of the hypothesis test (tcount = 4.824> ttable = 1.669), and the N-gain value of the experimental class (0.6487) was higher than that of the control class (0.5064). Thus, Ha is accepted, namely, the PBL-GI model effectively improves students' scientific literacy skills. The results of this study are expected to encourage teachers to design problem-based learning relevant to real life.